The Design Process towards Resource Productivity. A Case Study - Serena Baiani; Paola Altamura (Agathón)
The transition to a circular economy, applied as a priority to the built environment, is recognized in the most recent EU guidelines as a promising approach to increase resource productivity. In Italy, a powerful lever is represented by the mandatory application of the Minimum Environmental Criteria within Green Public Procurement which, in construction (Ministerial Decree 11/10/2017), concern the totality of the contracts. The paper describes one of the first complete implementations of these Criteria, considering the innovation in the design process from a life cycle perspective, which is reflected in particular in the methods of selection and procurement of natural and eco-friendly materials, with recycled content and certificated products, as well as in the design for disassembly of building components.